Spirituality trapped in androcentric celebrity cults in South Africa post-1994 - Kobo, Fundiswa Amanda (HTS teologiese studies, 2019)
This article makes a distinction between cultic spiritualties that are prevalent in South Africa and a womanist spirituality of liberation. The current trends related to celebrity lifestyles in post-1994 South Africa deeply suggest an erasure of our subversive memory rooted in our quest for liberation, infused with a culture of protest, the struggle for the affirmation of a black woman’s dignity and life. One of the biggest challenges we face in the rise of cultic worship in South Africa, this article will argue, is that spiritual malaise in a nation does not require argument and analyses albeit important, but a response that tames it with enhancing self-love and care and thus the development of the language and grammar of the soul – the rationality of the soul as propounded by Cone. The focus of this article will be on the ongoing Omotoso case as symbolic of these rapturous, pervasive life-killing forms of spirituality that a black womanist cannot be silent about. The article will show how celebrity culture traps our resources of spirituality we need to heal the nation that has been wounded but now continues with self-inflicted wounds two decades after its political liberation.